You should use the logarithmic identities such that:

`ln(xy) = ln x + ln y`

`f(x,y) = x*ln(xy) => f(x,y) = x*(ln x + ln y)`

`f(x,y) = x*ln x + x*ln y`

You need to find partial derivative `f_x` , hence, you need to differentiate the function with respect...

## See

This Answer NowStart your **subscription** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You should use the logarithmic identities such that:

`ln(xy) = ln x + ln y`

`f(x,y) = x*ln(xy) => f(x,y) = x*(ln x + ln y)`

`f(x,y) = x*ln x + x*ln y`

You need to find partial derivative `f_x` , hence, you need to differentiate the function with respect to x, keeping y constant, such that:

`f_x = ln x + x*1/x + lny`

`f_x = ln x + ln y+ 1 => f_x = 1 + ln(xy)`

You need to find partial derivative `f_y` , hence, you need to differentiate the function with respect to y, keeping x constant, such that:

`f_y = 0 + x*1/y => f_y = x/y`

**Hence, evaluating the partial derivatives yields `f_x = 1 + ln(xy)` and `f_y = x/y` .**